Умови сталого функціонування соціально-економічних систем - Petrov, E. G.; Gubarenko, I. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2013)
Properties and structure of social and economic system are described taking into account social, economic and ecological (noosphere) component. It allows comprehensively analyzing the system, allocating latent laws and synthesizing more effective models. The analysis of conditions of stability of social and economic systems is carried out and the approach to definition of a quantitative estimation of stability for more effective organization of management of systems of various hierarchical levels is offered. The way of indexation of characteristics of elements of social and economic system that allows to consider each characteristic separately is offered, but thus to keep understanding, at what hierarchical level it is in the general structure, it is connected with what elements, what generalizes or what part is. Ways of realization of management are analyzed by organizational systems. Features of application of various polynomial models for formation of the generalized estimations of stability are presented.